75 years of support for US priorities in the Western Hemisphere (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The Inter-American Institute for Cooperation on Agriculture (IICA) is uniquely positioned to help further US priorities in areas such as agricultural trade, biotechnology, food safety, animal and plant health, innovation, food security, and economic development throughout the Western Hemisphere.